Modeling of Dynamics of the Unemployment Index at the Regional Level by Means of the Spectral Analysis Method - Pleskach, Valentina (Lithuanian Journal of Statistics, 2014)
The model of the unemployment index at the regional level in accordance with the spectral analysismethod worked out by the team of О. Моrgenstein of American Princeton University is got. The unemployment indexes ofKovel town in Kovel district of Volyn region for the period of observations from January 1994 to February 2012 are theinformation basis of this research.